ExoMol line lists – XL. Rovibrational molecular line list for the hydronium ion (H3O+). Issue 2 (11th July 2020) - Yurchenko, S N; Tennyson, Jonathan; Miller, Steve; Melnikov, V V; O'Donoghue, J; Moore, L
ABSTRACT: A new line list for hydronium (H3 16 O + ) is computed. The line list is based on a new ab initio dipole moment surface (CCSD(T)/aug-cc-pVQZ) and a new empirical potential energy surface (PES). The empirical PES of H3 O + was obtained by refining an ab initio surface through a global fit to the experimentally determined rovibrational energies collected from the literature covering the ground, $ν _1^{± }$, $ν _2^{± }$, $2ν _2^{± }$, $ν _3^{± }$, and $ν _4^{± }$ vibrational states. The line list covers the wavenumber range up to 10 000 cm −1 (wavelengths $\gt 1 \, μ$ m) and should be complete for temperatures up to T = 1500 K. This is the first comprehensive line list for H3 O + with extensive wavenumber coverage and accurate transitional probabilities. Prospects of detection of hydronium in spectra of Solar system giant planets as well as exoplanets are discussed. The eXeL line list is publicly available from the ExoMol and CDS data bases.